Sistem Infomasi Pengaduan Masyarakat Desa Berbasis Android - Mutaqin, Roisyatul; Yusrotun, Anis; Sya'roni, Wahab (Universitas Trunojoyo Madura, 2021)
Public service is an important thing that must be considered in the development of an autonomous region, because it is directly related to the welfare of the community as well as in accordance with basic reforms in the field of government. However, community services in the Sumberanyar village, especially in terms of complaints such as complaints about social assistance, infrastructure and other complaints are still done manually and have not used an adequate system, where the Sumberanyar village community needs to come to the village office to convey their aspirations and complaints and in Sumberanyar village there is no means to convey aspirations and complaints so that public aspirations or complaints cannot be carried out optimally and data on community complaints are not well documented. Therefore, it is necessary to have an application that can make it easier for the community to make complaints, the Android-based information system for community service in Sumberanyar village, Paiton district, is a solution to overcome the problems that have been described. This application was built using the Waterfall SLDC (Software Development Life Cycle) model, from the results of this study it was concluded that the application is very suitable for use by the public to make complaints and convey aspirations and all features in the application can be used properly.